Recent Progress in the Topologies of the Surface Acoustic Wave Sensors and the Corresponding Electronic Processing Circuits - Mariya Aleksandrova; Dimiter Badarov (Sensors, 2022)
In this paper, we present an overview of the latest achievements in surface acoustic wave (SAW) sensors for gas or liquid fluid, with a focus on the electrodes’ topology and signal processing, as related to the application of the sensing device. Although the progress in this field is mainly due to advances in the materials science and the sensing coatings, the interdigital (IDT) electrodes’ organization is also an important tool for setting the acoustic-wave-distribution mode, and, thus, for improvement of the SAW performance. The signal-conditioning system is of practical interest, as the implementation of the SAW, as a compact and mobile system is dependent on this electronic circuit. The precision of the detection of the SAW platform is related not only to the IDT electrodes’ geometry but also to their location around the sensing layer. The most commonly used architectures are shown in the present paper. Finally, we identify the needs for the future improvement of these prospective sensors.